ANALISIS DEBIT SUNGAI BATANG SELO UNTUK KEBUTUHAN AIR IRIGASI DI KECAMATAN TANJUNG EMAS, KABUPATEN TANAH DATAR, PROVINSI SUMATERA BARAT - Rachmat Hidayat (Jurnal Teknik Sipil USU, 2019)
ABSTRACT  Provision of irrigation water in the area is often the case in the absence of a good setting so that the excess water supply regardless of the availability of water itself. In this case the water delivered to lands should be timely and the amount needed in the field.Batang Selo irrigation area is one of the technical irrigation under the management of Tanah Datar regency government in this case the Department of Infrastructure, which is currently implementing a rice-rice cropping this annually held since the completion of the construction of irrigation area of Batang Selo. Prediction of the increased demand for water in the future especially that accompanied the decline of water resources, it is necessary to anticipate early to water resources management strategies that exist for water to be used optimally. To optimize utilization of water resources of the river Batang Selo, then the efficiency of irrigation water use Batang Selo should be maximized.Implementation of the cropping pattern (rice-rice) today regardless of the availability of water each year lead to the use of water for irrigation is less efficient. Therefore in order to increase the efficiency of irrigation water use, need to be replicated on the application of cropping patterns that can improve the efficiency of irrigation water. Studies submitted through this thesis is to study the cropping pattern that can improve efficiency of irrigation water use by analyzing the planting patterns with few alternatives that can produce water balance maximal and efficient irrigation. Based on the results of the study found that the pattern of rice-rice-planting crops without an alternative class of 3 with the needs of the smallest water that is equal to 19.880 m3/dt/year can be applied and provide irrigation water efficiency and generate water balance that maxsimal and Cropping Intensity increased from the existing condition. Keywords: cropping, cropping intensity, efficiency, water availability, water balance.